2019
DOI: 10.1101/793083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Singing training predicts increased insula connectivity with speech and respiratory sensorimotor areas at rest

Abstract: The insula contributes to the detection and integration of salient events during goaldirected behavior and facilitates the interaction between motor, multisensory, and cognitive networks. Task-fMRI studies have suggested that experience with singing can enhance access to these resources. However, the long-term effects of vocal motor training on insula-based networks are currently unknown. In this study, we used restingstate fMRI to explore experience-dependent differences in insula co-activation patterns betwe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 203 publications
(278 reference statements)
4
6
0
Order By: Relevance
“…Several previous studies have explored the neural correlates of vocal expertise, revealing effects on regional activation and structure, as well as connectivity [34][35][36][53][54][55]. In the current study, we found a significant difference between singers and non-singer controls in the spoken imitation of VTL, and in the neural representation of this vocal parameter.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Several previous studies have explored the neural correlates of vocal expertise, revealing effects on regional activation and structure, as well as connectivity [34][35][36][53][54][55]. In the current study, we found a significant difference between singers and non-singer controls in the spoken imitation of VTL, and in the neural representation of this vocal parameter.…”
Section: Discussionsupporting
confidence: 64%
“…Neuroimaging studies have shown that primary somatosensory cortex is engaged by both overt and covert speech production [15] and thus could be implicated in both the planning and execution of laryngeal muscle activity. Evidence from highly-trained singers has identified regions of somatosensory cortex proximal to the dorsal LMC whose local activity [34], resting-state connectivity [35], and structure [36], are associated with singing experience. One interpretation of this finding is that it reflects the heightened control and somatosensory/kinesthetic awareness of vocal musculature that are associated with extensive musical training in voice [37].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have explored the neural correlates of vocal expertise, revealing effects on regional activation and structure, as well as connectivity [33][34][35][50][51][52]. In this study, we found a significant difference between singers and nonsinger controls in the behavioural imitation of VTL, and the neural representation of this vocal parameter.…”
Section: Discussionsupporting
confidence: 56%
“…A region of left somatomotor cortex identified in the whole participant group did not correspond topographically to previous reports of the larynx motor cortex (LMC). However, a further direct comparison of singers and controls revealed an expertise-related enhancement of VTL representation in right somatosensory cortex, just posterior to the reported location of the dorsal LMC in humans [16][17][18] and in line with a postcentral site previously linked to singing experience [33][34][35]. We speculate that this dorsal site could represent a larynx sensory cortex that is closely coupled to its corresponding LMC during speech motor control [9]: in line with this, probabilistic diffusion tractography analyses of LMC connectivity have revealed dramatically stronger connectivity with somatosensory and inferior parietal cortices in humans than in macaques [46].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation